Coculture of Human Mesenchymal Stem Cells and Articular Chondrocytes Reduces Hypertrophy and Enhances Functional Properties of Engineered Cartilage - Bian, Liming (Mary Ann Liebert, Inc., 2011)
Mesenchymal stem cells (MSCs) are being recognized as a viable cell source for cartilage repair; however, it still remains a challenge to recapitulate the functional properties of native articular cartilage using only MSCs. Additionally, MSCs may exhibit a hypertrophic phenotype under chondrogenic induction, resulting in calcification after ectopic transplantation. With this in mind, the objective of this study was to assess whether the addition of chondrocytes to MSC cultures influences the properties of tissue-engineered cartilage and MSC hypertrophy when cultured in hyaluronic acid hydrogels. Mixed cell populations (human MSCs and human chondrocytes at a ratio of 4:1) were encapsulated in the hydrogels and exhibited significantly higher Young's moduli, dynamic moduli, glycosaminoglycan levels, and collagen content than did constructs seeded with only MSCs or chondrocytes. Furthermore, the deposition of collagen X, a marker of MSC hypertrophy, was significantly lower in the coculture constructs than in the constructs seeded with MSCs alone. When MSCs and chondrocytes were cultured in distinct gels, but in the same wells, there was no improvement in biomechanical and biochemical properties of the engineered tissue, implying that a close proximity is essential. This approach can be used to improve the properties and prevent calcification of engineered cartilage formed from MSC-seeded hydrogels with the addition of lower fractions of chondrocytes, leading to improved clinical outcomes.